Unusual Susceptibility of Erwinia amylovora to Antibacterial Agents in Relation to the Barrier Function of its Cell Envelope - Chatterjee, Arun K. (1977)
Wild-type strains of the bacterial phytopathogen Erwinia amylovora (the cause of fire blight disease of apples and pears) are markedly susceptible to novobiocin, deoxycholate, and sodium dodecyl (= lauryl) sulfate. The inhibitory concentration, expressed as the concentration causing a 99% inhibition of growth, of these three antibacterial agents were 15 to 100, 40 to 800, and 50 to 800 μg/ml, respectively, depending on the E. amylovora strain. Growth of strains of other Erwinia spp. and Salmonella typhimurium is not affected at all, or is only slightly affected, at these concentrations. Introduction of the F′lac(+), RP1, and R100drd-56 (but not E-lac(+)) plasmids into an E. amylovora strain results in enhanced susceptibility to novobiocin and sodium dodecyl sulfate but not to deoxycholate. E. amylovora wild-type strains spontaneously release a periplasmic enzyme, cyclic phosphodiesterase, but not a cytoplasmic enzyme, glucose-6-phosphate dehydrogenase, into the growth medium. Addition of MgCl(2) (20 mM) and NaCl (84 mM) to tryptone broth stimulates the growth of wild-type E. amylovora strains and reduces or eliminates leakage of the periplasmic enzyme. Mutant strains of E. amylovora, selected for resistance to each separate antibacterial agent (or to all three of them), showed a direct correlation (in all but the novobiocin-resistant mutant) between drug resistance and reduced periplasmic leakiness. The relatively low maximum growth temperature (<37°C) of E. amylovora seems unrelated to periplasmic leakage, as judged from the inability of added MgCl(2) to raise the maximum growth temperature, although the generation time at 30°C is reduced from 108 to 54 min upon the addition of 20 mM MgCl(2). The extensive leakage of periplasmic enzyme and unusual drug susceptibility of E. amylovora strains might stem from some defect(s) in some cell envelope component(s) other than the lipopolysaccharide of these bacteria (which contain the usual liposaccharide constituents).